Formulasi Dan Uji Aktivitas Antibakteri Sediaan Sabun Transparan Ekstrak Gambir Terpurifikasi Kombinasi Vco Terhadap Bakteri Propionibacterium Acnes - LUSIA EKA PUTRI; Sefrianita Kamal; Laras Alhabil (Jurnal Penelitian Dan Pengkajian Ilmiah Eksakta, 2022)
One of the skin diseases that are often encountered by teenagers is acne. Acne is caused by several factors, one of which is a bacterial infection, namely the bacteria Propionibacterium acnes. One of the anti-acne preparations is anti-acne facial cleanser. Soap is formed from the reaction of saponification of triglycerides using alkali. One of the triglycerides that can be used in soap making is Virgin Coconut Oil (VCO). One of the anti-acne soap is transparent soap. To improve the quality of transparent soap preparations, in this study purified gambier extract was added. The polyphenolic compounds contained in this gambier extract are catechins which are antimicrobial and antioxidant compounds. Addition with variations in the concentration of purified gambier extract F0:0, F1: 0.25%, F2: 0.50% and F3: 0.75%. Soap was evaluated for its physical properties, namely pH, organoleptic, homogeneity, water content, high foam test, stability of preparation and antibacterial activity test against Propionibacterium acnes bacteria. Based on the research results, it is known that the purified gambir extract combined with VCO can be used as a transparent soap preparation that meets the requirements and has an inhibitory power against the bacteria Propionibacterium acnes ATCC 11827.